2011
DOI: 10.1212/wnl.0b013e31822cfc59
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal assessment of oxaliplatin-induced neuropathy

Abstract: Objectives:To characterize the natural history of oxaliplatin-associated neuropathy (ON) and determine whether intraepidermal nerve fiber density (IENFD) is a sensitive measure of neuropathy progression. In addition, we sought to assess the potential of ON as a neuroprotection model and gain insight into the relationship between axon loss and neuropathic symptoms.Methods: Eight subjects receiving oxaliplatin for advanced colorectal cancer were prospectively followed prior to starting chemotherapy and at 30, 90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
85
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 21 publications
9
85
0
Order By: Relevance
“…Burakgazi et al (29) have shown that the two best means of evaluating the severity of oxaliplatin neuropathy are through the use of clinical criteria and the distal leg intraepidermal nerve fiber density assay. The latter was not appropriate for our study, since the patients had grade ≥2 neuropathy at the time of inclusion and very likely had diminished nerve fiber density at the start of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Burakgazi et al (29) have shown that the two best means of evaluating the severity of oxaliplatin neuropathy are through the use of clinical criteria and the distal leg intraepidermal nerve fiber density assay. The latter was not appropriate for our study, since the patients had grade ≥2 neuropathy at the time of inclusion and very likely had diminished nerve fiber density at the start of the study.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by the sensory abnormalities such as unpleasant abnormal sensation (dysesthesia), an increased response to painful stimuli (hyperalgesia), and pain in response to a stimulus that does not normally provoke pain (allodynia) (Burakgazi et al, 2011). Peripheral neuropathic pain is observed frequently in patients with long standing diabetes, cancer, AIDS, leprosy, cervical disc protrusion, foraminotomy, and post-surgical event (Muthuraman and Singh, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Haematological toxicity is reversible, nausea and vomiting are preventable, whereas renal toxicity can be monitored. On the contrary, oxaliplatin-induced polyneuropathy is frequently irreversible and may even worsen after withdrawal of the drug, consistently compromising the quality of life in OAC survivors (26). In our experience, oxaliplatin-induced peripheral polyneuropathy occurs early in the adjuvant (postoperative) phase of perioperative treatment, leading to withdrawal of the drug.…”
Section: Discussionmentioning
confidence: 70%